Tourism Department Communication Strategy in Increasing the Positive Image of Tourism Destination Development in Asahan Regency - Riska Dwi*; Muhammad Alfikri (Riwayat: Educational Journal of History and Humanities, 2024)
This research examines how the Asahan district tourism office uses communication strategies to improve the positive image of tourist destinations in the region. The aim of this research is to understand the communication strategies used by the Asahan district tourism office in increasing the positive image of tourist destination development in the area. This research uses a qualitative method with a descriptive approach. Data was collected through direct observation and interviews with 5 informants, including the head of the tourism sector, canoe rowing tourism manager, mangrove tourism manager, bunkhouse tourism manager and visitors. The research results show that infrastructure development and good management of tourist groups are important to improve the positive image of tourist destinations. An active communication strategy between the Asahan district government, village heads and tourism awareness groups is needed for smooth tourism development. Good communication between relevant agencies in Asahan district is also needed, as well as the involvement of third parties as distributors of funds for developing tourist destinations. The Asahan district tourism office also uses social media Instagram and online websites to disseminate information about increasing the positive image of tourist destinations in Asahan district.